2001
DOI: 10.1074/jbc.m010291200
|View full text |Cite
|
Sign up to set email alerts
|

10E4 Antigen of Scrapie Lesions Contains an Unusual Nonsulfated Heparan Motif

Abstract: The carbohydrate antigen on heparan sulfate recognized by monoclonal antibody 10E4 is uniquely codistributed with the abnormal prion protein, PrP Sc , even in the earliest detectable brain lesions of scrapie-infected mice. Determining the chemical structure of 10E4 antigen is, therefore, an important aspect of structure elucidation of scrapie lesions, and a prerequisite for designing experiments to understand its role in scrapie pathogenesis. Toward this aim, we have examined preparations of heparan sulfate, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 35 publications
1
52
1
Order By: Relevance
“…In these scenarios TGs have been implicated in the abnormal accumulation of insoluble and protease-resistant proteinaceous aggregates (14). In addition, HS is co-distributed with the abnormal prion protein, PrP(Sc), even in very early disease stages in scrapie-infected mice (41). This raises the possibility that HS may also serve as a scaffold for protein aggregation in these pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In these scenarios TGs have been implicated in the abnormal accumulation of insoluble and protease-resistant proteinaceous aggregates (14). In addition, HS is co-distributed with the abnormal prion protein, PrP(Sc), even in very early disease stages in scrapie-infected mice (41). This raises the possibility that HS may also serve as a scaffold for protein aggregation in these pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…10E4 antibody is a widely-used antibody for the detection and localization of heparan sulfate in tissues. [26][27][28] Leteux et al 29 reported that 10E4 recognized a heparan sulfate tetrasaccharide in which an N-unsubstituted GlcN residue was required for the binding to 10E4. More recently, it was shown that a mixed N-sulfated/Nacetylated epitope was necessary for 10E4 binding.…”
Section: Discussionmentioning
confidence: 99%
“…Two HS-specific monoclonal antibodies were tested, one of which (JM-403) (29) is directed against an epitope containing GlcNH 3 ϩ . The HS epitope of the other monoclonal (10E4) has been proposed to comprise the sequence HexUA-GlcNH 3 ϩ -HexUA-GlcNAc (32). N-Acetylation of free amino groups blocked the reactivity of JM-403 (Fig.…”
Section: Resultsmentioning
confidence: 99%